Performance Enhancement of a Three Phase Boost-Cascaded Fifteen Level Inverter Using the PI Controller. (19th May 2022) - Sathish Kumar, S.; Ramkumar, R.; Sivarajeswari, S.; Ramya, D.; Subburaj, T.; Sankoh, Martin
Abstract : Photovoltaic power generation is a potential alternative energy source that offers several benefits over other alternative energy sources such as wind, sun, ocean, biomass, geothermal, and so on. Multilevel inverters are essential for power conversion in solar power generation. These multilevel inverters employ three distinct topologies: diode-clamped (neutral-point clamped) inverter, capacitor-clamped (flying capacitor) inverter, and cascaded H-bridge multilevel inverter. The cascaded H-bridge multilevel inverter is more appropriate for photovoltaic applications than the other two topologies. The proposed system asymmetrical cascaded multilevel inverter (ACMLI) is energized using a photovoltaic system (PV). A three-phase cascaded H-bridge fifteen-level inverter for grid-connected solar systems is given in this study utilizing a proportional integral controller. The harmonic distortion was removed using a multicarrier pulse width modulation method. The MATLAB/Simulink is used to simulate the performance of a three-phase cascaded H-bridge fifteen-level inverter in terms of harmonic content and number of switches. To test the performance of the designed system, a hardware prototype was created. From the obtained results, the proposed method reduces the switch count, harmonic distortion, and rejects the external disturbances of input and output variables.